Associations between peer motivational climate and athletes` sport-related well-being: Examining the mediating role of motivation using a multi-level approach - Isoard-Gautheur, S.; Ginoux, C.; Trouilloud, D. (Journal of Sports Sciences, 2022)
The objective is to examine the links between peer motivational climate (peerMC) and sport-related well-being (SRWB), and the mediational role of motivation in these relationships. Seventy-three athletes aged 18-25 years completed questionnaires on peerMC, motivation, burnout and engagement, every week for one month. Linear Multilevel Models revealed that task peerMC significantly predicted autonomous motivation at the within- and between-person level, burnout and engagement at the within-person level. Moreover, autonomous motivation was identified as a mediator of the relationship between task peerMC and burnout at the within-person level, and task peerMC and engagement at the within- and between-person levels. Ego peerMC significantly predicted autonomous motivation at the within-person level and controlled motivation at the between-person level. Autonomous motivation was also confirmed as a mediator of the relationship between ego peerMC and burnout, and between ego peerMC and engagement at the within-person level, and controlled motivation was also confirmed as a mediator of the relationship between ego peerMC and burnout at the between-person level. The results confirm that a task-oriented peerMC is likely to lead to the most positive consequences for athletes in terms of motivation and SRWB, whereas the ego-driven climate leads to more negative consequences.